A response to the terms in Shah et al's 'Neurodevelopmental disorders and neurodiversity: definition of terms from Scotland's National Autism Implementation Team'. (April 2023) - Chown, Nick; Annable, Jennifer Layton; Beardon, Luke; Howard, Nik
Abstract : The Scottish National Autism Implementation Team's neurodiversity terms are a valiant, but flawed, attempt to reconcile different worldviews on neurodiversity. The aim of harmonising different perspectives is laudable; however, we disagree with the use of 'societal norms' in the authors' framework of terms and challenge some of their proposed definitions.